Assessing Response Using Tc99m-MIBI Early after Interstitial Chemotherapy with Carmustine-Loaded Polymers in Glioblastoma Multiforme: Preliminary Results. (27th March 2014) - Cecchin, D.; Schiorlin, I.; Della Puppa, A.; Lombardi, G.; Zucchetta, P.; Bodanza, V.; Gardiman, M. P.; Rolma, G.; Frigo, A. C.; Bui, F.
Abstract : Introduction . Early signs of response after applying wafers of carmustine-loaded polymers (gliadel) are difficult to assess with imaging because of time-related imaging changes. Tc 99 m -sestamibi (MIBI) brain single-photon emission tomography (SPET) has reportedly been used to reveal areas of cellularity distinguishing recurrent neoplasm from radionecrosis. Our aim was to explore the role of MIBI SPET in assessing response soon after gliadel application in glioblastoma multiforme (GBM). Methods . We retrospectively reviewed the charts on 28 consecutive patients with a radiological diagnosis of GBM who underwent MIBI SPET/CT before surgery (with intracavitary gliadel placement in 17 patients), soon after surgery, and at 4 months. The area of uptake was selected using a volume of interest that was then mirrored contralaterally to obtain a semiquantitative ratio. Results . After adjusting for ratio at the baseline, the effect of treatment (gliadel versus non-gliadel) was not statistically significant. Soon after surgery, however, 100% of patients treated with gliadel had a decreased ratio, as opposed to 62.5% of patients in the non-gliadel group P = 0.0316 . The difference between ratios of patients with radical versus partial resection reached statistical significance by a small margin P = 0.0528 . Conclusions . These data seem to suggest that the MIBI ratio could be a valuable tool for monitoring the effect of gliadel early after surgery.